2006
DOI: 10.1084/jem.20060244
|View full text |Cite
|
Sign up to set email alerts
|

IL-23 stimulates epidermal hyperplasia via TNF and IL-20R2–dependent mechanisms with implications for psoriasis pathogenesis

Abstract: Aberrant cytokine expression has been proposed as an underlying cause of psoriasis, although it is unclear which cytokines play critical roles. Interleukin (IL)-23 is expressed in human psoriasis and may be a master regulator cytokine. Direct intradermal administration of IL-23 in mouse skin, but not IL-12, initiates a tumor necrosis factor–dependent, but IL-17A–independent, cascade of events resulting in erythema, mixed dermal infiltrate, and epidermal hyperplasia associated with parakeratosis. IL-23 induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
506
1
10

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 622 publications
(552 citation statements)
references
References 55 publications
26
506
1
10
Order By: Relevance
“…2a). In the experiment of intradermal IL-23 injections to mouse ear skin, another widely used model of psoriasiform skin inflammation, IL-17A/IL-17F/ IL-22 expression was upregulated after IL-23 injection 33,35 , and adiponectin deficiency further increased their expression level (Fig. 2b).…”
Section: Resultsmentioning
confidence: 98%
“…2a). In the experiment of intradermal IL-23 injections to mouse ear skin, another widely used model of psoriasiform skin inflammation, IL-17A/IL-17F/ IL-22 expression was upregulated after IL-23 injection 33,35 , and adiponectin deficiency further increased their expression level (Fig. 2b).…”
Section: Resultsmentioning
confidence: 98%
“…In sum, these studies demonstrate several key aspects of IL-23/T H -17 pathobiology related to psoriasis: (1) Both IL-12p40 and IL-23p19 mRNA expression levels are significantly elevated in both nonlesional psoriatic skin versus normal skin as well as lesional psoriatic skin versus non-lesional psoriatic skin. 37,38 (2) (5) clinical studies have shown dramatic efficacy of IL-12p40 antibodies in reducing symptoms in a high percentage of psoriatic subjects 44,45 and those with active Crohn's disease. 46 These diverse studies have conspired to highlight the central function of the IL-23/T H -17 axis in mediating chronic inflammatory disease pathogenesis, downplaying the role of IL-12.…”
Section: Discussionmentioning
confidence: 99%
“…The disease is typified by overproliferation of keratinocytes and recruitment of immunocompetent cells, including CD4 þ T lymphocytes, to the dermal tissues generating chronic inflammation. 1 Affecting joints and surrounding tissues in 10-30% of psoriatic patients, inflammatory arthritis markedly impacts mobility and can cause irreversible joint destruction. Several genetic and epidemiological studies have demonstrated that Crohn's disease, cardiovascular disease and possibly metabolic syndrome are comorbid with psoriasis, particularly with more severe, earlier onset psoriasis.…”
Section: Introductionmentioning
confidence: 99%
“…IL-23 is involved in the pathobiology of numerous chronic diseases, including colitis, encephalitis, psoriasis, rheumatoid arthritis and cancer 12,14,15,34 , and is critical for the survival of T H -17 cells 12,30 . These T cells release IL-17A, a cytokine that increases production of several proinflammatory molecules, including IL-1 and TNF 35 .…”
Section: Discussionmentioning
confidence: 99%
“…T H -17 cell population expansion and survival depends upon IL-23, which like IL-17 has been linked to the pathobiology of chronic inflammatory diseases [12][13][14][15] . IL-17 is present in asthmatic airways, can induce lung inflammation and stimulate mucus production [16][17][18][19][20][21][22][23] .…”
Section: Introductionmentioning
confidence: 99%